Liability claims under the Warsaw and Montreal Conventions : a case study of a fictitious South African passenger of the German Wings Flight 9525 of 24 March 2015 - Hobe, Stephan (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2016.